Direct calculation of the dimerization constant of water molecules for a dense water vapor - Bulavin, L.A.; Makhlaichuk, P.V.; Khrapatiy, S.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The dimerization constant for a dense water vapor is determined from the direct calculation of the internal statistical sums of monomers and dimers. The obtained results are compared to the experimental data and the results of calculations that are based on the relation between the dimerization constant and the second virial coefficient.